Efeitos de intervenção com tecnologias educativas para promoção da autoeficácia materna em amamentar: ensaio clínico randomizado - Sousa, Janaina Landim de (2021)
Maternal self-efficacy to breastfeed is a modifiable variable, which can be stimulated by educational strategies that aim to increase the self-efficacy of mothers in promoting exclusive breastfeeding for their children. The aim was to evaluate the effectiveness of using the serial album “I can breastfeed my baby” together with a brief motivational interview to promote maternal self-efficacy in breastfeeding. This is a randomized controlled clinical trial, with two groups: intervention group (IG) and control group (CG), carried out with 152 postpartum women in rooming-in with their newborn babies at a reference maternity hospital in Fortaleza, Ceará. Data collection took place in two phases: 1. application of the Breastfeeding Self-Efficacy Scale – ShortForm (BSES SF) and a sociodemographic form for both groups in rooming-in. Also, at this stage, an intervention was carried out with the serial album associated with a brief motivational interview with the IG; 2. application of the BSES-SF scale and the breastfeeding investigation form (BF) by telephone in six follow-up (at the 15th, 30th, 60th, 90th, 120th and 180th day of the child's life). Double-blind was guaranteed. The contrasting groups were analyzed and an association was made between maternal self-efficacy in breastfeeding and sociodemographic variables with the Chi-Square and likelihood ratio tests. The strength of this association was calculated using the odds ratio (OR). Their means were compared, according to sociodemographic variables, using Student's t test, ANOVA, Mann-Whitney and Kruskal-Wallis. Data were processed using the Statistical Package for Social Sciences (SPSS) version 20. The project was registered and approved by the Brazilian Registry of Randomized Clinical Trials (REBEC) and by the Research Ethics Committee of the Assis Chateaubriand Maternity School. The groups were homogeneous at baseline for sociodemographic, obstetric, current pregnancy and breastfeeding history variables. In the intervention group, there was an increase in the number of participants who presented high self-efficacy from baseline to 180 days of life. There was also a statistically significant association between the intervention and control groups in relation to the mean self-efficacy scores at baseline until 90 days of follow-up. The means of the BSES-SF scores in the six moments did not differ statistically in the control group, while in the intervention group, the means were statistically significant (p<0.0001). The practice of exclusive breastfeeding up to 180 days of follow-up was higher in the IG when compared to the CG, and it can also be seen that the chances of not breastfeeding exclusively in the CG ranged from 1.5 to 0.8 more of the women in the GI. Regarding the self-efficacy scores in breastfeeding and the child's dietary pattern, a statistically significant association can be seen in the intervention group at all times analyzed (p < 0.001), and at 15, 30 and 60 days of the babies lives there was greater significance specifically to exclusive breastfeeding (p < 0.001), noting higher mean breastfeeding self-efficacy scores in IG. It is concluded that the educational intervention proposed based on the application of the serial album “I can breastfeed my baby” together with a brief motivational interview was an effective strategy to increase maternal self-efficacy in breastfeeding and extend the days of exclusive breastfeeding.